Formulation, analysis and plant design for coal water slurry fuel blended with wastewater - Mueed Akhtar (NUST201463513MCES6411F); Dr Muhammad Zubair (USPCAS-E, NUST, Islamabad, 2016)
TH-59
Keywords: MS-ESE Thesis MS Thesis